2017
DOI: 10.1021/acsnano.6b07471
|View full text |Cite
|
Sign up to set email alerts
|

Growth Rates and Spontaneous Navigation of Condensate Droplets Through Randomly Structured Textures

Abstract: Dropwise condensation is a phenomenon of common occurrence in everyday life, the understanding and controlling of which is of great interest to applications ranging from technology to nature. Scalable superhydrophobic textures on metals are of direct relevance in improving phase change heat transport in realistic industrial applications. Here we reveal important facets of individual droplet growth rate and droplet departure during dropwise condensation on randomly structured hierarchical superhydrophobic alumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(129 citation statements)
references
References 44 publications
5
124
0
Order By: Relevance
“…In principle, any sub-microscale structures with a small feature size (tip size and interspace) and a certain height (or depth) can become effective candidates for creating CMDSP surfaces. In fact, except for arrays of closely packed nanotips, including nanocones, [22,27,50,69,70] nanoneedles, [21,28,31,66,71] nanopencils, [23] and tip-like nanotubes, [72,73] other architectures such as nano wires, [24,74] nanosheet arrays, [20,29,62,75] nanorod-capped nano pores, [68,76] the porous structure of nanoparticles, [67] nanoparticle aggregates, [73,[77][78][79][80] and two-tier structures [25,57,63,[81][82][83][84][85][86][87][88][89] have all been verified to be effective in endowing material surfaces with the desired CMDSP functionality as long as they follow these basic construction rules.…”
Section: Construction Rules Of Bionic Cmdsp Surfacesmentioning
confidence: 99%
“…In principle, any sub-microscale structures with a small feature size (tip size and interspace) and a certain height (or depth) can become effective candidates for creating CMDSP surfaces. In fact, except for arrays of closely packed nanotips, including nanocones, [22,27,50,69,70] nanoneedles, [21,28,31,66,71] nanopencils, [23] and tip-like nanotubes, [72,73] other architectures such as nano wires, [24,74] nanosheet arrays, [20,29,62,75] nanorod-capped nano pores, [68,76] the porous structure of nanoparticles, [67] nanoparticle aggregates, [73,[77][78][79][80] and two-tier structures [25,57,63,[81][82][83][84][85][86][87][88][89] have all been verified to be effective in endowing material surfaces with the desired CMDSP functionality as long as they follow these basic construction rules.…”
Section: Construction Rules Of Bionic Cmdsp Surfacesmentioning
confidence: 99%
“…Also, the technique should be easy to implement in ambient conditions. Optical microscopy (Chu et al 2017;Nilsson and Rothstein 2011), and environmental scanning electron microscopy (ESEM) (Anand and Son 2010;Barkay 2013;Rykaczewski et al 2011;Sharma et al 2017) are some of the observation techniques that have been reported in the literature for dropwise condensation visualization.…”
Section: Introductionmentioning
confidence: 99%
“…22 The gradually expanding upper portion of a PW condensate leads to a decreasing capillary pressure therein whereas its tail portion remains under high capillary pressure. Thus-generated internal pressure gradient 23,24 would pull the condensate tail upward, and at a specic size the droplet base would detach from the rst tier valley, leading to self-pulling (or self-jumping) of the stretched PW droplet without coalescence. The self-pulling mode has been recently reported by Aili et al 6 in their study of condensation on nanostructured microporous surfaces.…”
Section: Theoretical Modelsmentioning
confidence: 99%